Toyota's knowledge-sharing intention in Brazil and Japan: does organisational cross-culture matter? - Muniz, Jorge; Popadiuk, Silvio; Batistela, Gislaine Cristina; Nakanishi, Fabio K.; Rodriguez, Indira Arias [UNESP] (Taylor & Francis Ltd, 2022)
This study evaluated whether the organisational culture of the country causes a moderating effect on the relationship between motivational factors and knowledge sharing intention (KSI) from the perspective of Toyota managers in Japan and Brazil. The questionnaire applied to Toyota managers, in Brazil (n = 84) and Japan (n = 111) through online access. The data treatment applied structural equation modelling. The results revealed that Brazilian managers attributed higher mean values than the average values of Japanese managers. Analysis of the two samples revealed no significant differences in the structure of the structural equation model through the use of PLS-PM. While for the Brazilian sample only anticipated reciprocal relationship explained KSI, for the Japanese sample, the anticipated reciprocal relationship and sense of self-worth contributed to explaining KSI. Three interactions between the three moderation variables and the three independent variables were significant when analysing the sample of Brazilian managers.
Keywords: Motivational factors; organisational culture; knowledge sharing intention; Japan; Brazil; Toyota